The Principle of Geodemocracy and its impact on FDI, global supply chain and global sourcing - Bharrien, Kevin (Digital Repository of Theses - SSBM Geneva, 2024)
This dissertation investigates the intricate dynamics of Geodemocracy in the contemporary world, focusing on the interplay between geopolitics, power, and policy in shaping global political landscapes. By employing a multidisciplinary approach, the study integrates perspectives from political science, geography, international relations, and economics to offer a comprehensive analysis. The research begins with a theoretical framework that revisits classical Geodemocracy Theory and contextualizes them within modern realities, then study the impact of Geodemocracy Theory on foreign direct investment (FDI), global supply chain (GSC) and global sourcing (GS) around the world, and focuses on how to mitigate potential uncertainties and risks. The Geodemocracy Index (GMI) is a combined tool to dynamically estimate risks from three major pillars: democracy, economy and geopolitics, which might be utilized by business practitioners as an indicator for international business activities. The dissertation also explains how GMI functions: • What is geodemocracy? • How does the GMI impact FDI, global supply chain, and global sourcing? • How do business practitioners mitigate risks when executing FDI, GSC, and global sourcing by using GMI analysis?